A short theory of the error process. (December 2021) - Ruhm, Karl H.
Abstract: In spite of endless discussions about uncertainties the debate about errors is less animated. It makes sense to define a general error process as a sub-process within any erroneous real world process. This can be done in a top down concept by an appropriate model, usable in any practical application with the help of scientific adaptation. The following introduction is primarily based on theoretical considerations.